A Design of Educational Multimedia Software for Disability: A Case Study for Deaf People - Mazlina, Abdul Majid; Ananthi, Krishnasami Masitry; Herawan, Tutut (2012)
This paper focuses on develop a new multimedia courseware for disabilities students mainly for students who have hearing problem. This application can be used by deaf pupils to learn sign language by watching video and animation pictures to communicate with other deaf people. This system will be providing the student to select the alphabetical and see the picture and the sign language explanation. The student also allows selecting the number and picture to view and with the sign language explanation. With the navigation provide to e-MSL allow the student to access with easily.